2013
DOI: 10.1017/s1368980013001006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversification for prevention of anaemia among women of childbearing age from rural India

Abstract: Objective: To assess the impact of an intervention modifying dietary habits for the prevention of anaemia in rural India. Design: Intervention study with data on anthropometric (weight, height) measurements, Hb and diet pattern. As per the cut-off for Hb in the government programme, women with Hb ,11 g/dl had to be given Fe tablets and formed the supplemented group while those with Hb . 11 g/dl formed the non-supplemented group. Settings: Three villages near Pune city, Maharashtra, India. Subjects: Rural non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…A recent review by Lassi et al [41] showed that iron supplements could significantly improve hemoglobin concentration in adolescents. Efforts should also be steered towards nutritional programs that promote dietary diversity in order to improve the content and bioavailability of micronutrients in household diets [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Lassi et al [41] showed that iron supplements could significantly improve hemoglobin concentration in adolescents. Efforts should also be steered towards nutritional programs that promote dietary diversity in order to improve the content and bioavailability of micronutrients in household diets [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable efforts to decrease its prevalence, the health and nutritional status of adolescents has seen limited improvement over the past 50 years (8,17). Although diet related health problem affects both sexes and all age groups, it is a major public health problem among women (18) especially among adolescent girls (19).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating therapeutic (deworming) and preventive (either food-based or WASH/malaria education) strategies can simultaneously treat infections and increase hematopoietic micronutrient intake or reduce disease transmission, which could result in the reduction of malnutrition and anemia [2,14,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Several comprehensive intervention strategies have correspondingly been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Several comprehensive intervention strategies have correspondingly been tested. However, they frequently evaluate the impact of education on nutrition or on infectious etiologies (whether or not combined with drug therapy) separately [17,18,19,20,21,22,23,24,25,26,27,28,29,31]. Thus, differences in their designs and methodologies hinder the comparison and evaluation of results, rendering it difficult to define the best approach to reduce anemia.…”
Section: Introductionmentioning
confidence: 99%